Molecular characterization of the staphylococcal multidrug resistance export protein QacC. - Paulsen, I; Brown, M; Dunstan, S; Skurray, R (1995)
The QacC polypeptide is a member of a family of small membrane proteins which confer resistance to toxic compounds. The staphylococcal qacC gene confers resistance to toxic organic cations via proton-dependent export. The membrane topology of the QacC polypeptide was investigated by constructing and analyzing a series of qacC-phoA and qacC-lacZ fusions. From these analyses, most of the predicted features of the QacC protein were verified, although data regarding the possible orientation of the COOH region were not conclusive. The role of the sole cysteine residue, Cys-42, in QacC was studied by using the sulfhydryl reagent N-ethylmaleimide and site-directed mutagenesis. N-Ethylmaleimide was shown to inhibit qacC-mediated ethidium export. Multiple amino acid substitutions were made for Cys-42, and mutations at this location had various effects on resistance specificity. This suggests that the Cys-42 residue may be located near a region of QacC that is involved in substrate recognition. Mutagenesis of conserved residues in QacC indicated that Tyr-59 and Trp-62 also play an essential structural or functional role in QacC.